Shams o Toghra,, compatibility in connection and struggle of old and new - Mohammad Ragheb (تاریخ ادبیات)
The first Persian historical novel, Shams o Toghra (Kermanshah: 1288-1289 AH / 1327-1328 AH) by Mohammad Baqer Mirza Khosravi (1266-1338 AH), takes place in the time of the Salghurids and provides a space for struggle between old and new ideas, techniques, and forms in six areas of linguistic and intertextual relations, literary genre, narration system, characterization, time and place, and politics and compatibility. The main question is what is the position of Shams o Toghra during the formation of modern Persian literature? Is it a modern or traditional work? Is it opening a new way in the field of Persian fiction? On the one hand, in spite of all the innovation, it is still not possible to create a new form, such as the Siyahat-Name-ye Ibrahim Beyg by Zain al-Abedin Maraghi, because the work lacks problematic hero. But on the other hand, the image of the author's contemporary world is reflected on the events and through it, the existing conflicts in the society are represented; Conflicts that end in one-sided compatibility. In fact, although the historical novel does not create a new form, it is a mirror to the contemporary world. Generally in almost all of the areas listed, the struggles are overpowering, and Shams o Toghra cannot be considered as a modernist work.